Expression of phosphatase and tensin homolog, epidermal growth factor receptor, and Ki-67 in astrocytoma: A prospective study in a tertiary care hospital - Rajdeep Saha; Uttara Chatterjee; Sonali Mandal; Kaushik Saha; Sandip Chatterjee; Samarendra Nath Ghosh (Indian Journal of Medical and Paediatric Oncology)
Background: Though the tumor grade is a key factor influencing the choice of therapies, particularly determining the use of adjuvant radiation and specific chemotherapy protocols, role of abnormality in phosphatase and tensin homolog (PTEN) expression and variation in epidermal growth factor receptor (EGFR) labeling index (LI) and Ki-67 LI in survival and clinical outcome have been studied by many researchers in the recent past. Aims: The aim was to evaluate the expression of PTEN, EGFR and Ki-67 in different grades of astrocytic tumors by means of immunohistochemistry and to judge their role in overall survival (OS). Materials and Methods: This study was conducted on 57 cases of different grades of astrocytomas. Expression of PTEN, EGFR and Ki-67 was assessed by immunohistochemistry on formalin fixed and paraffin-embedded sections and the OS was evaluated by Kaplan-Meier survival curves and log-rank test for 2.5 years from the date of primary resection. Results: Most of the tumors (59.6%; 34 cases out of 57) displayed WHO Grade IV features. Distribution of age, EGFR LI and Ki-67 LI expressed strong positive (≥0.5) correlation with the grade of tumors. However, the PTEN positivity was inversely related with the grade of the tumors. Lower WHO grades, lower values of Ki-67 LI, EGFR LI and PTEN positivity were associated with better survival. Conclusion: Expression of PTEN, EGFR LI and Ki-67 LI should be combined with the basic histopathological features including WHO grade to predict the prognosis and therapeutic outcome.